(untitled) (Bangladesh Journal of Medicine, 2021)
Roseomonas gilardiii a species of Gramnegative, strictly aerobic, coccobacilli-shaped, pink-pigmented bacterium pathogenic for humans, causing rare cause of bacteremia and other infections especially who are immunosuppressed .These bacterias are detected after several days growth in culture, and typical pink, mucoid colonies are found.In this case infective endocarditis in a patient due to roseomonas gilardii and the clinical course with isolation of the organism in Bangabandhu Sheikh Mujib Medical University (BSMMU)is reported. Bangladesh J Medicine July 2022; 33(1) : 109-113